Psychoemotional sphere of spouces whose husbands have schizophrenia of different terms - Herasymuk, V. A. (Journal of Education, Health and Sport, 2017)
The objective: to study the state of the psycho-emotional sphere in the spouses of paranoid schizophrenia (PS) husbands with different duration of the disease. Object of the research: 120 women with mentally insane husbands and 50 spouses of men without metal and behavioral disorders have been examined. The examination was performed on the basis of Communal Health Protection Institution "O. I. Yushchenko Vinnitsa Regional Psychoneurological Hospital”. The comprehensive examination included clinical, psychological, psychodiagnostic and statistical methods. Results. The study found that in almost all spouses of PS men, regardless of the duration of the disease, there is an increased level of neuroticism, which is an unfavorable factor and evidences of pathopersonic transformations attributable to this contingent. For the vast majority of the women under examination, regardless of the duration of their husbands’ disease, a violation of the psycho-emotional sphere in the form of affective anxiety-depressive manifestations are typical, unlike the wives of mentally healthy men. In the structure of depressive response in wives of men with any duration of PS, the ratio of affective-cognitive and somatic symptoms is close, unlike the symptoms of the anxiety circle, in the structure of which the manifestations of "psychic" radical significantly outweigh the somatic symptoms. Intensity and polymorphy of affective anxiety-depressive symptoms and signs in spouses of PS men is directly associated with the duration of the disease, i. e., with increasing duration of illness in men, there is an increase in psychopathological manifestations of their wives. Conclusion. The data obtained should be taken into account in the development of personalized measures of psychocorrection and psychoprophylaxis of disorders of psycho-emotional sphere in the spouses of PS men.